The Impact of Local Culture on Teaching and Learning Practices in Makassar's Elementary Schools - Mahesa, Abdi; Setiawan, Rizal; Ma’ruf, Amar (Educia Journal, 2023)
A research project investigates how Makassar primary schools integrate local cultural elements into their teaching practices and affects the student participation level as well as their learning outcomes and cultural skills acquisition. The research utilized a qualitative research design through teacher interviews and classroom observation sessions to determine how local culture and language along with practices get integrated into curricular content. The concept of culturally relevant teaching proves effective in student engagement as well as representing an essential element for social relationship development among generations. Restrictions emerged regarding proper integration of cultural material into national educational requirements while experts judged that additional backing along with teacher training would be vital. The present study delivers critical knowledge regarding culturally responsive education by examining an older system from a non-Western context to support teachers and educational administrators